The role of ethnicity on pain perception in labour among parturients at the University College Hospital (2009)
Aims: In developing countries, the major mechanism by which parturients cope with labor pain is psychological. This study aims to assess the effect of ethnicity on the perception of pain by parturients in labor at the University College Hospital, Ibadan. Materials and Methods: The study was conducted between the 1 November 2006 and the 30 March 2007 at the University College Hospital Ibadan. The main outcome measure was pain perception assessed by the Box Numerical Scale (BNS). Univariate analysis was by t-test for continuous variables and c2 test for categorical variables. The multiple linear regression method was utilized for multivariate analysis. The level of statistical significance was set at P < 0.05. Results: The lowest adjusted mean BNS score was found in theYoruba ethnic group: they had scores lower than the mean scores for the other ethnic groups (-0.636 [95% confidence interval (CI) -0.959, -0.313]). The presence of a doula also reduced the mean BNS scores significantly (-0.533 [95% CI -0.844, -0.222]. Increasing parity also reduced pain scores (-0.182 [95% CI -0.342, -0.022]). Increasing educational attainment increased pain scores in labor (0.189 [95% CI 0.017, 0.361]). The influence of increasing age was not statistically significant in this model. In conclusion, ethnicity of the parturient relative to that of the predominant ethnicity in the place of birth has a significant effect on the perception of labor pain by the parturient. In our resource-challenged environment, trained doulas may help make labor less painful for the parturient